Modifications of the maximum expiratory flow in bronchial asthma treatment using Intal and Ketotifeno. - Belkis M. Vicente Sánchez; Nallelys Villanueva Bravo; Luis M. Padrón Velásquez; Marylin Aroche Quintana (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Introduction: The studies of the lung function are essential for the diagnosis, classification and treatment of the Bronchial Asthma and inside them the mensuration of the flow maximum expiratory (FEM) it provides a quantitative value of the obstruction of the air roads. Methods: It was carried out a study in two stages, the first one descriptive in which was included the 15 year-old patients and more with diagnostic of Bronchial Asthma and belonging to the CMF #26 of the Policlínico Area V of the Municipality Cienfuegos, with the objective of determining the modifications of the value of the FEM according to outline of treatment used intercrisis. The sample was constituted for 37 patients, to those that were applied a form of data where it was included the age, sex, clinical characteristics of its illness and the current treatment. In the second stage two groups were created selected by the simple random method. The first one received treatment with Intal Spray (four aplications per day) and the second with Ketotifeno (tab. 1 mg. /2tab par day) egining to make mensurations from FEM to the three, six, nine and twelve months of having implemented the treatment. Results: They in our patient prevailed the ages of 15- 24 years and of 25- 34 years and the feminine sex, the Salbutamol was the more utilized in the previous treatments, initially the greater number of asthmatic they were classified like moderates and upon concluding the 12mo month the 72.9% they of the total of the pattern behaved like light; they with both treatments improved the courages of FEM, although the group of patient that you received treatment with Intal you showed an improvement in statements security much more rapid. Conclusions: That patient that they utilized Intal had a more rapid elevation of the FEM.